Interpretative complexity and tax law changes: the taxation of corporate expenses in Portugal. Issue 4 (12th November 2018) - Martins, António; Dinis, Ana; Lopes, Cidália
Abstract : Purpose: Autonomous taxation of expenses (ATE) is a special and contentious feature of corporate income taxation in Portugal. By taxing of an expanding set of corporate expenses, it has caused many conflicts between the Portuguese tax authority and corporate taxpayers. Many of these conflicts emerged from the legal interpretation of ATE's clauses, while others derived from frequent, and difficult to apply, legislative changes. The purpose of this paper is to focus on the following research question: does the recent evolution of the rules on ATE show an efficient process of making and interpreting tax law in Portugal? The authors intend to analyze the process of making and changing ATE's rules, as well as to study how interpretative complexity increases conflicts between tax authorities (TA) and taxpayers. Design/methodology/approach: The methodology used is a mix of the legal research method, namely, doctrinal methodology, with an analysis of jurisprudential and arbitration trends in litigation rulings, blended with the case study analysis of ATE in Portugal. Arbitration rulings will have a particular relevance to the analysis. Findings: The main conclusion is that, urged by the need of revenues, and sensitive to the TA' argument of ATE's loopholes, the government hastened to close them. However, given the procedure adopted, new legal questions aroused, creating additional layers of complexity for companies, courts and tax auditors. Constitutional issues were highlighted by companies based on the prohibition of retroactive application of tax laws. Research limitations/implications: The paper has a conceptual nature and its conclusions cannot be automatically extended to other tax controversies or processes of amending tax laws. However, for the legal and accounting professions it offers valuable lessons in law interpretation and political lobbying to change tax laws. Also, in the international tax scene, some countries also introduced ATE, with potential for similar problems. Practical implications: Regarding ATE's streamlining, the process recently observed in Portugal was not, in authors' view, managed in the best way, leaving a significant number of difficulties to be solved by courts. The change in ATE's legal framework could have been more carefully managed, avoiding costly and time consuming disputes, in order to minimize compliance costs. Originality/value: The paper contributes to the literature because this Portuguese experience, while highlighting the difficulties in making tax law, can be seen as a lesson on how to improve these processes, avoiding time and costs for business, TA and courts. Moreover, arbitration is a way of solving tax disputes that has been gaining ground in Portugal. In this respect, the paper also contributes to a better perception of the tax arbitration scenario in anEuropean Union country. It is also important for the accounting profession, whose members have often to deal with tax topics and the interpretative complexities they originate.